IDENTIFIKASI PENYEBAB DAN TEKNIK PENURUNAN SUSUT ENERGI LISTRIK MENGGUNAKAN METODE FAILURE MODE END EFFECT ANALYSIS PADA PT PLN (PERSERO) ULP KANGEAN MADURA - Gumintang, Adnan; Dhofir, Moch.; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
PT PLN (Persero) is one of the state-owned enterprises responsible for managing electricity in Indonesia. PLN playsa crucial role in providing electricity services to the community through generation, distribution, and sales. At PT PLN(Persero) ULP Kangean, there are 33,737 customers with a connected load of 2,278,050 VA. However, there is adiscrepancy between the amount of energy sold and the amount of energy issued during this period. Two maincomponents, namely technical and non-technical components, are the two factors behind this energy loss. The FailureMode and Effect Analysis (FMEA) method is used in this study to identify the causes of electrical energy loss. Dataanalysis conducted from January to September 2022 shows that the Low Voltage Network (JTR) is the main cause ofelectrical energy loss at PT PLN (Persero) ULP Kangean. There are several failures in the JTR, where damage to theelectrical conductors is one of the contributors to the highest Residual Risk Priority Number (RPN), namely 23.1 or31.37%. This error is a major concern in efforts to repair and control energy loss. This study provides valuable insightsinto the main sources of energy loss at PT PLN (Persero) ULP Kangean, and enables the implementation of more preciseand efficient actions to improve the efficiency of electricity distribution and address failures that can cause energy loss. Keywords — Electrical Energy Shrinkage; PT PLN (Persero) ULP Kangean; FMEA; JTR; distribution cable